2017
DOI: 10.1172/jci97015
|View full text |Cite
|
Sign up to set email alerts
|

CXCL11-dependent induction of FOXP3-negative regulatory T cells suppresses autoimmune encephalomyelitis

Abstract: The Editors recently became aware that some of the flow cytometry plots in this article were duplicated and used to represent different samples. Specifically, in Figure 5C, the flow cytometry plots of IFN-γ-and IL-17-stained cells from IgG1-and CXCL10-Ig-treated animals are from the same sample. In addition, in Figure 7A, the spinal cord samples from the PBS-and IgG1-treated animals are the same; the spleen samples from the CXCL11-Ig-and IgG1-treated animals are the same; and the lymph node samples for the PBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 0 publications
2
34
0
1
Order By: Relevance
“…Changes in epigeneticcontrol mechanisms may allow for switching between exhausted and activated T cell states. In addition, T reg cells can be converted into T H 17 cells in the presence of IL-6 and TGF-β 46,47 , which might underlie certain forms of autoimmunity, such as autoimmune hepatitis and psoriasis 48,49 , and CXCL11 promotes T reg cell differentiation into CXCR3 + CD4 + effector T cells, suggesting that it might be involved in the development of autoimmune encephalitis 50 . Control of T reg cell plasticity is further regulated by EZH2, a target for multiple small-molecule inhibitors in cancer trials 51 .…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
“…Changes in epigeneticcontrol mechanisms may allow for switching between exhausted and activated T cell states. In addition, T reg cells can be converted into T H 17 cells in the presence of IL-6 and TGF-β 46,47 , which might underlie certain forms of autoimmunity, such as autoimmune hepatitis and psoriasis 48,49 , and CXCL11 promotes T reg cell differentiation into CXCR3 + CD4 + effector T cells, suggesting that it might be involved in the development of autoimmune encephalitis 50 . Control of T reg cell plasticity is further regulated by EZH2, a target for multiple small-molecule inhibitors in cancer trials 51 .…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
“…Recently it has been shown that the ligands for CXCR3 induce different effects. Although it has been established that CXCL10 and, to a slightly lesser extent, CXCL9 are pro-inflammatory, CXCL11 has been shown to induce the development of Tregs (regulatory T-cells) and thus is anti-inflammatory (25). These findings support therapeutic targeting of a ligand as opposed to the promiscuous receptor, highlighting that the more appropriate question may be to find the right target for a given indication (26).…”
mentioning
confidence: 98%
“…CCL17 also induces calcitonin-gene related peptide expression much more efficiently than CCL22 (15). In a more recent study, Karin and co-workers (16) showed that CXCL9/10 binding to CXCR3 biased T cell polarization into Th1/Th17 effector cells, whereas CXCL11 binding drives T cell polarization into IL-10 producing Treg, and they linked this behavior to differences in STATs activation. In contrast, for other receptors such as CCR2 or CCR5, the apparent selectivity of chemokines for one particular pathway appears relatively subtle (9,10).…”
mentioning
confidence: 99%